Análise econômico-financeira de instituições financeiras: um estudo comparativo aplicado aos bancos comerciais e múltiplos do sistema financeiro nacional - Martins, José Geraldo (2007)
The main purpose of this master s dissertation is to apply the economic/financial analysis techniques to consecutive balance sheets and income statements of commercial and multiple banks in the Brazilian financial system, in constant currency, and to analyze the results obtained. In order to achieve that main purpose, we realized a conceptual and theoretical review of the financial intermediation system, especially the components financial markets and institutions and the interest rates and their term structures and yield curves. We also effected a review of the account plan for the Brazilian financial system institutions, with special emphasis on the general accounting standards, list of accounts and their functions and basic structures of published balance sheets and income statements. In addition, we reviewed management concepts and practices applied to financial institutions as well as economic/financial analysis indicators adapted to financial statements of financial institutions. Although focused on an academic research where we recorded the views of some authors on the main concepts, restrictions and techniques related to the subject, we also expressed our own opinion in some situations based on personal experience acquired in specific segments of the Brazilian financial system over time. In the empirical testing we applied the methods of horizontal and vertical analysis of balance sheets, economic/financial indices and value-added indicators to the balance sheets and income statements of six major commercial and multiple banks in the Brazilian financial system for the fiscal year of 2004 and 2005, in 2005 purchasing power. The trial reveals that the analysis of financial institutions in the Brazilian financial system conducted on the published financial statements is effective, despite the limited information contained on the annual abridged accounting reports